Estimation of dynamic load demand on a ground support scheme due to a large structurally controlled violent failure – a case study - Drover, C.; Villaescusa, Ernesto (2016)
© 2015 Institute of Materials, Minerals and Mining and The AusIMM Published by Maney on behalf of the Institute and The AusIMM. In the future a larger proportion of underground mines will operate in deep, high stress environments where excavations may be exposed to very high loading demands. This case study has examined a violent structurally controlled failure occurring in a deep hardrock underground mine at a depth of 1055 metres below surface. On the basis of the damage observations the back analysis of this event concludes that the surface support system was ejected from the wall of the excavation with an initial velocity of 10.7 m s-1. Estimates of the mechanical demand imparted to the ground support scheme during failure were also calculated. These estimates carry several assumptions in order to simplify complex uncertainties concerning the loading mass of rock and transfer of kinetic energy between the rock and ground support. However, the demand may be conservatively assumed to be at least 150 kJ m-2. These results may reflect future mining conditions at great depth.